Avaliação do sistema de gestão de energia em empresas brasileiras com geração fotovoltaica: uma proposta de ferramenta de análise de gap - Boesing, Patrícia (2019)
The use of renewable energy sources in the domestic industry is in its phase of industrial power generation and energy control seems to account for 41% of the country's electricity consumption. In order to confront the paradox of energy efficiency and the use of renewable energy sources, results have been found that demonstrate a feasibility of using renewable energy in the industrial sector. For many Brazilian managers, energy efficiency and the energy management system are the same and, due to this thinking, there is still little diffusion of the principles of energy management and its application. In order to increase the use of energy management practices, this study identified the shortcomings of the electric energy management system present in Brazilian companies that photovoltaic generation interconnected to the utility's grid. To do this, a questionnaire was prepared to measure the level of maturity of energy companies. Validated as a tool, based on a non-parametric statistical analysis. With the help of the validation of the questionnaire, it was possible to determine the level of maturity of a company in the companies participating in the research, as well as determine which are its partners to develop and improve their level of energy management. The best method to measure manager responses to a tool was also determined. For this purpose, it can be useful to increase the energy generated and consumed by them. Therefore, in order to be able to apply the investment and para-purposes applications, they must be applied by the company.